1992
DOI: 10.1051/limn/1992013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of several biological indices based on river macroinvertebrate benthic community for assessment of running water quality

Abstract: Nine biological indices based on the macroinvertebrate community inhabiting rivers have been calculated in order to find out which of them is more appropriate to evaluate the qualitative status of the running water for public environmental authorities. The BMWP' score (Alba-Tercedor & Sânchez-Ortega 1988) has been chosen because it is both accurate and precise, and easy to calculate. Some problems derived from sampling strategies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
0
15
0
4
Order By: Relevance
“…These early studies established strong correlations between the individual assessment methods and compared the methods directly. This approach towards intercalibration was then followed by various authors both to demonstrate the relationship of methods and to point out discrepancies between national quality classifications (Ghetti & Bonazzi, 1977;Rico et al, 1992;Friedrich et al, 1995;Biggs et al, 1996;Morpurgo, 1996;Stubauer & Moog, 2000). In their preparatory study for the Water Framework Directive Nixon et al (1996) explicitly recommended direct comparison to be used for the intercalibration of assessment methods.…”
Section: Introductionmentioning
confidence: 99%
“…These early studies established strong correlations between the individual assessment methods and compared the methods directly. This approach towards intercalibration was then followed by various authors both to demonstrate the relationship of methods and to point out discrepancies between national quality classifications (Ghetti & Bonazzi, 1977;Rico et al, 1992;Friedrich et al, 1995;Biggs et al, 1996;Morpurgo, 1996;Stubauer & Moog, 2000). In their preparatory study for the Water Framework Directive Nixon et al (1996) explicitly recommended direct comparison to be used for the intercalibration of assessment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if equivalent reference conditions have been identified for a site then the comparison of the site score with the predicted or the actual score of the reference site may provide a cost-effective, easily applicable and understandable evaluation of the water quality, consistent with the requirements of the WFD. Nevertheless, biotic indices and scores have to be scientifically accurate, simple and practicable as to their application (Rico et al, 1992) as well as adapted to the typology of the water bodies and the special conditions of a country. Consequently, the new Hellenic Evaluation Score and its Interpretation Index were produced being based on easily collected samples a) from all seasons reflecting any kind of seasonal effect, b) from different substrate types and c) with different habitat characteristics representing some of the System B parameters of the WFD characterizing river typology.…”
Section: Discussionmentioning
confidence: 99%
“…Alba-Tercedor and Sanchez-Ortega (1988), Interpretation B of BMWP' proposed by Rico et al (1992), AQEM classification (Skoulikidis et al, 2004).…”
Section: Comparison With Other Scores and Classification Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological quality was determined using the IBMWP index (Alba-Tercedor and Sánchez-Ortega 1988), which has been widely applied in the Iberian Peninsula and provides a value resulting from the sum of values attributed to key macroinvertebrate families according to their tolerance to organic pollution. Besides the inherent simplicity (Rico et al 1992), it showed to be efficient in quantifying the organic enrichment. In order to overcome the inherent weakness of the IBMWP system, namely the direct influence of sampling effort, the Average Score per Taxa (ASPT) was calculated (Armitage et al 1983).…”
Section: Biological Assessmentmentioning
confidence: 99%